Evaluation of Students’ Research Activities in the Design Study Programmes at Rezekne Higher Education Institution - Mežinska, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays education and research is promoting development of design industry. In order to find unique Latvian design identity the quality of design is increasing. New possibilities and requirements for design education and research are raised by social and ecological issues. In order to promote sustainable design education research strategy is needed, therefore it is essential to pay attention to research strategy in education process. The aim of the article is educational research as significant part of research competence theoretical and empirical evaluation and its activation in design courses' education process in Rezekne Higher Education Institution. The analysis of the learning research process was carried out in accordance with the principles of action research, theoretical researches in the context of the issue were carried out and the results were obtained: opinions of 80 full time students in the age group 19-25 years, about the role of learning research process of designers' education. The research has practical meaning, because it recommends suggestions for perfection of study process in connection to investigation and analysis of educational research promoting/delaying activities, and necessity to promote students' research competence for professional project work in the future.